Loss Aversion, Regret Aversion, Herding in Fraudulent Investment Decisions Moderated by Financial Literacy - Nugraha, Muhammad Ardian Satya; Wahyuni, Asri Nur (KEUNIS, 2025)
Fraudulent investment schemes continue to deceive the public despite ongoing improvements in financial literacy across Indonesia. This phenomenon presents a serious threat to personal financial management, as many individuals are still lured by promises of unrealistic profits and pressured into high-risk financial traps. These schemes exploit specific psychological vulnerabilities that influence decision-making. This study aims to examine the influence of three behavioral loss aversion, regret aversion, and herding on fraudulent investment decisions, with financial literacy analyzed as a moderating variable. Total of 100 respondents in Semarang who had experienced financial losses due to fraudulent investment practices were selected using purposive and snowball sampling methods. Data were analyzed using feasibility tests, classical assumption testing, multiple regression analysis, and moderated regression analysis (MRA). The findings reveal that loss aversion and regret aversion both have a significant negative effect on fraudulent investment decisions, while herding has a positive influence. Additionally, financial literacy plays a quasi-moderating role, effectively weakening the impact of these psychological traits. These findings underscore the importance of psychological factors in irrational financial behaviors and highlight the critical need for improved financial literacy education. Strengthening financial awareness may help reduce vulnerability to deceptive investment offers and promote healthier financial decision-making.